Engineered electrospun poly(lactic-co-glycolic acid)/Si3N4 nanofiber scaffold promotes osteogenesis of mesenchymal stem cell - Zhou, Changsong; Su, Shenghui; Fan, Jiwen; Lin, Jiuzao; Wang, Xiaoyong (Frontiers in Materials, 2022)
Nanofibers show promise as bone tissue engineering scaffolds (BTESs). In this study, electrospun poly (lactic-co-glycolic acid) (PLGA)/silicon nitride (Si3N4) composite nanofiber membranes were formed and the osteogenesis capability of mesenchymal stem cells (MSC) from the scaffold marrow was investigated. By modifying the different properties of Si3N4 in the PLGA, two hybrid scaffolds were successfully prepared, including the PLGA/Si3N4 (1 wt.%) nanofiber scaffold and PLGA/Si3N4 (2 wt.%) nanofiber scaffold. The diameter of the fiber nanofiber scaffold PLGA/Si3N4 was decreased and the mechanical strength was increased compared to PLGA. In vitro studies showed better cell adhesion and proliferation on the PLGA/Si3N4 nanofiber scaffold compared to the PLGA nanofiber scaffold. The integration of Si3N4 promoted osteogenesis capacity by increasing the gene expression of bone-related proteins (BMP2, ALP, OPN, COL1a1, Runx2, and OCN), calcium deposits, and support of ALP activity compared to those for the PLGA nanofiber scaffold. Similarly, the PLGA/Si3N4 (2 wt.%) nanofiber scaffold showed better mechanics and biological activity compared to the PLGA/Si3N4 (1 wt.%) nanofiber scaffold. Overall, the PLGA/Si3N4 nanofiber scaffold showed potential as a promising hybrid scaffold for bone regeneration.